2020
DOI: 10.3892/etm.2020.9183
|View full text |Cite
|
Sign up to set email alerts
|

miR‑590‑5p may regulate colorectal cancer cell viability and migration by targeting PDCD4

Abstract: Recent studies have revealed that microRNAs (miRs) are involved in the pathogenesis of colorectal cancer (CRC); however, the roles of miR-590-5p in CRC are not completely understood. Therefore, the present study investigated the expression of miR-590-5p and programmed cell death 4 (PDCD4) in CRC tissues and healthy adjacent tissues via reverse transcription-quantitative PCR. Furthermore, human CRC cells were cultured in vitro and transfected with miR-590-5p inhibitor. CRC cell viability, migration and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…MiR-590 is located near the long arm of chromosome 7 of human genome, and its function remains elusive. Existing research has reported that miR-590 shows abnormal expressions in various tumors and diseases 15,16) . For example, Cai et al 17) identified that miR-590-5p was able to inhibit the mRNA expression of its target gene signal transducer and activator of transcription 3 (STAT3) through the luciferase reporter system, and that STAT3 was only expressed in osteosarcoma tissues and cells, exhibiting great effects in the invasion and infiltration of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-590 is located near the long arm of chromosome 7 of human genome, and its function remains elusive. Existing research has reported that miR-590 shows abnormal expressions in various tumors and diseases 15,16) . For example, Cai et al 17) identified that miR-590-5p was able to inhibit the mRNA expression of its target gene signal transducer and activator of transcription 3 (STAT3) through the luciferase reporter system, and that STAT3 was only expressed in osteosarcoma tissues and cells, exhibiting great effects in the invasion and infiltration of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, miRNAs influence major signaling pathways in CRC, as discussed in Section 2, resulting in changes in tumor phenotype [99]. For example, miR-590-5p was overexpressed in CRC patient tissues and cell lines and was verified to directly regulate the expression of PDCD4, thereby reducing its expression [100]. It was confirmed that the decreased miR-590-5p induced the expression of PDCD4, resulting in modulating the expression of TGF-β and SMAD2/3, genes involved in the TGF-β signaling pathway.…”
Section: Mirna Regulationmentioning
confidence: 99%
“…338 Programmed cell death 4 (PDCD4) is a tumor-suppressor protein that can inhibit the progression of CRC cells. 339,340 The IL-6/STAT3 axis increases the expression of miR-181b which in turn reduces PDCD4 expression and prevents apoptotic cell death. Besides, IL-6/STAT3/miR-181b/PDCD4 axis increases metastasis of CRC cells.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Upregulation of IL‐17C is suggested to promote CRC progression through the activation of STAT3 signaling and subsequent elevation of miR‐23a‐3p expression which leads to angiogenesis induction via VEGF upregulation 338 . Programmed cell death 4 (PDCD4) is a tumor‐suppressor protein that can inhibit the progression of CRC cells 339,340 . The IL‐6/STAT3 axis increases the expression of miR‐181b which in turn reduces PDCD4 expression and prevents apoptotic cell death.…”
Section: Ncrnas and Stat3 Regulation In Gastrointestinal Cancersmentioning
confidence: 99%